1992
DOI: 10.1246/cl.1992.2289
|View full text |Cite
|
Sign up to set email alerts
|

First Isolable tert-Alkyl Phenyl Selones

Abstract: The reaction of the dihydrazone of 2,2,6,6-tetramethyl-1,7-diphenyl-1,7-dione with Se2Cl2 in refluxing benzene in the presence of tributylamine gave the corresponding 1-oxo-7-selone and 1,7-diselone derivatives in 14 and 33% yields, respectively, while similar reaction of the dihydrazone of 2,2,5,5-tetramethyl-1,6-diphenyl-1,6-dione gave bicyclic 1,3-diselenetane (25%), 1,2,4-triselenolane (20%), and cyclohexene (12%) derivatives by intramolecular cyclizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We previously observed that the diphenyl analogue 29 reacted with Se 2 Cl 2 in the presence of ( n -Bu) 3 N to produce the cyclohexene 30 along with the bicyclic selenium compounds 31 and 32 . The 1,3,4-selenadiazoline 33 was proposed as the intermediate for 30 …”
Section: Resultsmentioning
confidence: 99%
“…We previously observed that the diphenyl analogue 29 reacted with Se 2 Cl 2 in the presence of ( n -Bu) 3 N to produce the cyclohexene 30 along with the bicyclic selenium compounds 31 and 32 . The 1,3,4-selenadiazoline 33 was proposed as the intermediate for 30 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the dithiirane oxide 4 decomposes on heating to give the thioketone 10 and 6 11 Ph& 12 Thermal isomerization of 4 to 5 was also observed; heating a solution of 4 in toluene-ds at 110 OC for 0.5 h gave a mixture of 4, 5, 10,6, and 7 in the ratio of 62:9:7:17:6. in a stereospecific manner.…”
Section: P G ! ) +mentioning
confidence: 99%
“…Interestingly, treatment of a chloroform solution of 1a with SnCl 4 at refluxing temperature afforded an epimeric mixture of 1,2,4-triselenolanes 8a (10%, approximately 1:1 mixture) [36][37][38][39] along with the formation of selenocarbamate 9a (25%), diselenide 4 (14%), and a trace amount of 6a. A similar reaction of a chloroform solution of 1e with SnCl 4 at refluxing temperature just gave a small amount of solvent-insoluble polymeric compound, characterizable to be polymethylene selenide (10e, approximately 20%) [40][41][42][43][44][45][46][47] by using IR spectrum, along with an unstable compound characterized by novel 1,2,4,5-tetraselenane (11e, approximately 4%).…”
Section: Formation Of β-135-triselenanes 6 By Treating Diselenoacetmentioning
confidence: 99%